Identifying and overcoming challenges in the EMA’s qualification of novel methodologies: a two-year review - Drmić, Ana; Saccà, Riccardo; Vetter, Thorsten; Ehmann, Falk (Frontiers in Pharmacology, 2024)
The EMA Qualification of Novel Methodologies procedure qualifies methods, technologies and methodologies within a well-defined context of use in a pharma R&D context based on the evaluation of the presented scientific rationale and submitted data. This policy brief analyses QoNM submissions providing policy messages and recommendations to stakeholders on how to better prepare qualification applications in this regard. The recommendations include: 1. Grounding validation strategy using a current standard measure or a distribution technique. 2. Accurately represent pertinent subgroups via accurate inclusion and exclusion criteria. 3. Establish a well-defined and specific CoU with clear descriptions of the use within a development program target population and disease stage. Lastly, it emphasizes role of the QoNM procedure in advancing medicine development methodologies within the EU.